Epstein-Barr Virus Infection and Increased Sporadic Breast Carcinoma Risk: A Meta-Analysis - Jin, Qing'e (Med Princ Pract, 2020)
OBJECTIVE: An association of Epstein-Barr virus (EBV) infection with breast carcinoma (BC) risk has so far been disputed in the literature. Therefore, we performed a meta-analysis to clarify this relationship. MATERIALS AND METHODS: An electronic database search for eligible case-control studies was performed using PubMed, Embase, Web of Science, the Cochrane Library, CNKI, and Wanfang Data until May 17, 2018. The pooled OR and 95% CI were used to estimate the relationship between EBV infection and BC risk using a fixed or random-effects model depending on heterogeneity. Subgroup analysis and meta-regression were used to explore the heterogeneity. Publication bias was assessed using Egger's and Harbord's tests. RESULTS: A total of 16 studies with 1,279 patients and 814 controls were reviewed based on our inclusion and exclusion criteria. Compared with the control group, EBV infection had a significant association with BC risk (OR 4.75, 95% CI 2.53–8.92, p < 0.01) with significant heterogeneity observed (I2 = 65.3%). The subgroup analysis revealed that region and tissue type might explain potential sources of heterogeneity. The sensitivity analyses yielded stable results. No significant publication bias was observed. CONCLUSION: The current results suggest that EBV infection is significantly associated with increased risk of BC.